2018
DOI: 10.1002/mnfr.201800808
|View full text |Cite
|
Sign up to set email alerts
|

Extract of the Microalga Nitzschia laevis Prevents High‐Fat‐Diet‐Induced Obesity in Mice by Modulating the Composition of Gut Microbiota

Abstract: Scope The aim of the present study is to investigate the efficacy of Nitzschia laevis extract (NLE) in preventing obesity in mice fed with a high‐fat diet (HFD), and the potential underlying mechanisms focusing on modulation of the gut microbiota profile. Methods and results Physiological, histological, and biochemical parameters and gut microbiota compositions are compared among four experimental groups fed respectively with the following diets for 8 weeks: Normal chow diet, HFD, HFD + low concentration of NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…5), resulting in maintaining intestinal epithelium integrity. This is consistent with the previous study, which reported that increased expression of occludin and ZO-1, along with modulation of the gut microbiota composition, contributed to strengthen the gut integrity and barrier function [48]. The results suggest that PEW may improve obesity-related metabolic disorders by modulating gut microbiota and maintaining intestinal epithelium integrity.…”
Section: Discussionsupporting
confidence: 93%
“…5), resulting in maintaining intestinal epithelium integrity. This is consistent with the previous study, which reported that increased expression of occludin and ZO-1, along with modulation of the gut microbiota composition, contributed to strengthen the gut integrity and barrier function [48]. The results suggest that PEW may improve obesity-related metabolic disorders by modulating gut microbiota and maintaining intestinal epithelium integrity.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we checked the expression of genes related to the de novo synthesis of endogenous fatty acids, including Srebp-1c and FAS [38][39][40]. Although it had been reported that the expression of Srebp1-c and FAS were increased in HFD-fed mice [2,41], some studies showed the opposite result [42,43]. Our results were consistent with the later findings.…”
Section: Discussionsupporting
confidence: 89%
“…At the phylum level, NAR supplementation decreased the Firmicutes/Bacteroidetes ratio in HFD-fed mice (Figures 6A-C). Consistently, several reports revealed that polyphenols and Chinese herbal extracts, such as Nitzschia laevis extract (Guo et al, 2019), Citrus aurantium L. var. amara Engl.…”
Section: Discussionsupporting
confidence: 68%